THE EFFECTIVENESS OF WARNING IN TELEVISION ADVERTISING - Maysoon Kadhim Jasim; Mohammed Nori Dheyab (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Warning methods in television advertisements represent a wide area at the level of employment and expression of the subject of advertisement. In light of the technical developments, these methods have an aesthetic value in the structure and formulation of the contents and ideas presented at work, which enhances the value of the advertisement as it has various and many forms. The aesthetic and expressive value of working through these methods provides us with a warning against the use of a particular commodity or product and a warning of the consequences that may be afflicted by the consumer. And I chose a research topic entitled The Effectiveness of Warning Methods in Television Advertising, and the purpose was to demonstrate the effectiveness of warning methods to create a work with content that reaches the recipient, then a section The research is divided into four chapters. The first is the methodological framework, containing the research problem, which is a question, how effective are the warning methods in television advertising? As well as the importance, goal and limits of the research, in addition to defining the search terms that were received, and the terms effectiveness - methods - and advertising have been identified.